Democracy and education: Notes over military training in Argentina and Brazil - Ana Penido; Suzeley Kalil Mathias; Eduardo Mei. (Íconos)
This article assumes that the countless military interventions and coups, and the decades in which both Argentina and Brazil lived under dictatorships; constitute an obstacle for democracy and reveal the importance of educating soldiers on the importance of military subordination to civilian authorities. Four major findings can be derived from the above assumptions, i) a new educational approach is unavoidable if military autonomy is to be overcome and if military subordination to civilian authorities is to take root; ii) Military education is also crucial in the training of competent military leaders, able to fulfill their duties to the countries they serve; iii) Military autonomy hampers democratic consolidation and international cooperation in defense issues; iv) Reducing the differences between military training and the civilian educational system facilitates operational defense policies and fosters the internalization of democratic values into the ranks. The differences found between the Argentinian and Brazilian cases clearly illustrate the dilemmas involved in military education. Thus, it seems useful to subject both countries to a comparative study of their opposing experiences. In order to achieve this, a military education matrix is used. The matrix is composed of four quadrants: normative, relational, teaching systematics and internal. This article focuses in the normative quadrant and shows that Brazil´s current military training is clearly behind Argentina’s in applying changes supportive of democratic transition.